MULTIVARIATE OPTIMIZATION OF MICROWAVE-ASSISTED ENZYME DIGESTION OF α-CASEIN FOR GENERATION OF BIOACTIVE PEPTIDES - Katherine López; Alejandra Espinoza-Bello; Jonathan Carrasco; Carlos Peña-Farfal; Mario Aranda; Karem Henriquez Aedo (Journal of the Chilean Chemical Society, 2023)
Caseins are the principal milk proteins and serve as an important source of bioactive peptides with diverse beneficial effects for human health, such as antihypertensive, immunomodulating, anti‐inflammatory, and antithrombotic. The objective of this study was to optimize, using the design of the experiment, the production of bioactive peptides from α-casein applying microwave-assisted enzyme digestion (MAED). The optimal MAED conditions (time, temperature, and enzyme/protein ratio) were established for pepsin (digestion time 4 min, temperature 41°C, and E:P ratio 1:40) and trypsin (digestion time 10 min, temperature 37°C and E:P ratio 1:200.) enzymes. Digestion yields and the intensity of different bioactivities, i.e., antimicrobial, antioxidant, and acetylcholinesterase and α-glucosidase inhibitory activities, evaluated by the HPTLC-bioassay technique were used as response variables. Trypsin-formed α-casein peptides showed antimicrobial, antioxidant, and acetylcholinesterase inhibition activities, while pepsin-formed showed antimicrobial, antioxidant, and α-glucosidase inhibition activities. These results demonstrate that MAED is a fast and effective technique for bioactive peptide production from casein proteins.